TRANSGENERATIONAL TRAUMA a contemporary introduction. - Salberg, Jill.; Grand, Sue. ([S.l.] : ROUTLEDGE, 2024)
In this book, Jill Salberg and Sue Grand offer an overview of the psychoanalytic work on transgenerational trauma, rooting their perspective in attachment theory, and the social-ethical turn of Relational psychoanalysis. Transgenerational Trauma: A Contemporary Introduction is a cutting-edge study of trauma transmission across generations. Salberg and Grand consider how our forebears' trauma can leave a scar on our lives, our bodies, and on our world. They posit that, too often, we re-cycle the social violence that we were subjected to. Their unique approach embraces diverse psychoanalytic and psychodynamic theories, as they look at attachment, legacies of violence, and the role of witnessing in healing. Clinical and personal stories are interwoven with theory to elucidate the socio-historical positions that we inherit and live out. Social justice concerns are addressed throughout, in a mission to heal both individual and collective wounds. Transgenerational Trauma: A Contemporary Introduction offers a nuanced and comprehensive approach to this vital topic, and will be of interest to psychoanalysts, psychologists and other mental health professionals, as well as students and scholars of trauma studies, race and gender studies, sociology, conflict resolution, and others.
Keywords: Psychic trauma; Psychotherapy; PSYCHOLOGY / Mental Health